Putting Gestures to Work: Georges Didi-Huberman, Uprisings - Longford, Sam (Kronos: Southern African Histories, 2021)
Georges Didi-Huberman’s Uprisings is at once heavy and light. It weaves complex (and sometimes burdensome) political traditions and histories of thought concerned with uprising, rebellion and revolution, with bursts of poetry which, it seems, are meant to take flight off the page like the butterfly tracts that Didi-Huberman so admires. It is also vast in its scale and depth, tracing histories of uprising and rebellion from Atlas, Prometheus and Eve, through to future uprisings which are as yet unknown and, as the author reminds us, endless: ‘the uprising is a gesture without end’.